Role of diffusion weighted imaging and dynamic contrast enhanced magnetic resonance imaging in breast tumors - Magda Ali Hany El Bakry; Amina Ahmed Sultan; Nahed Abd Elgaber El-Tokhy; Tamer Fady Yossif; Carmen Ali Ahmed Ali (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Purpose: To evaluate the role of diffusion weighted imaging and dynamic contrast enhanced magnetic resonance imaging in characterization of breast tumors and comparing the results with the histological finding. Patients and methods: From January 2011 to January 2015, 71 patients with 74 suspicious breast lesions had performed breast DCE-MRI combined with DWI and the results were compared with the histopathological examination which was used as the standard diagnostic method. Results: The study included 71 patients with 74 suspicious breast lesions, there were 38 benign lesions ((51.35%) and 36 malignant lesions (48.65%)). DCE-MRI proved to have a sensitivity of 91.7%, and a specificity of 84.2%. ADC cutoff value to differentiate between benign and malignant lesions was 1.32 × 103 mm2/s (P < 0.001). The diffusion weighted MRI proved to have a sensitivity of 94.4%, and a specificity of 92.1%. The combined MRI protocol of DCEMRI and DWI proved to increase the sensitivity and specificity of breast MRI. Conclusion: DWI had a higher sensitivity and specificity than DCE-MRI. The combined MRI protocol of DCEMRI and DWI proved to increase sensitivity and specificity of MRI in diagnosis and differential diagnosis of breast lesions.